TANTANGAN GURU KELAS DALAM MENGAJAR SISWA BERKEBUTUHAN KHUSUS PADA SD NEGERI 2 BATULO KOTA BAUBAU - Mawar Eka Septian; La Jusu; Madi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research employed a qualitative approach with a case study design, where data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, with validity tested through source and technique triangulation. The findings reveal that classroom teachers face multilayered challenges encompassing a pedagogical dimension in the form of difficulty designing learning that accommodates two groups of students simultaneously, a psychological dimension in the form of sustained emotional pressure arising from a continuous dual burden, and a structural dimension characterized by the absence of special companion teachers, individualized learning programs, and adequate inclusive system support. Amid these limitations, teachers developed adaptive strategies grounded in personal initiative, including informal differentiation, individual guidance outside class hours, and proactive communication with parents. This study affirms that structural reinforcement of the inclusive education system is an urgent necessity to realize quality and equitable education for all children, in alignment with the mandate of SDGs Goal 4.